Implementing bilingual pattern practice - Scheffler, Paweł (My University, 2016)
This article describes how semi-communicative bilingual drills were implemented in a four-month course in pedagogical English grammar. In the course, a group of ten Polish adult learners participated. When the course was over, the learners were asked to evaluate the procedure by filling in a questionnaire. In the questionnaire, they expressed overwhelming approval for bilingual drills in terms of their usefulness. Some of the students indicated that the drills prepared them for communication in English.
Keywords: pattern practice; semi-communicative drills; English grammar teaching; native language in teaching English